Three Pillars of Sustainable Development: Challenges versus Achievements - Ghimire, Bidhya Jyoti (Journey for Sustainable Development and Peace Journal, 2023)
This study provides an in-depth exploration of the challenges and achievements associated with the three pillars of sustainable development, namely economic growth, social equity, and environmental protection. Utilizing qualitative research designs, along with the utilization of secondary sources and data collection techniques, this study aims to offer a comprehensive and scholarly understanding of the intricate dynamics inherent in these pillars. Drawing upon an extensive array of scholarly articles, and reports from reliable secondary sources, this research identifies and critically analyzes the salient challenges prevailing within each pillar. This study delves into the nuanced experiences and perspectives of diverse stakeholders engaged in sustainable development initiatives globally. This encompasses a comprehensive assessment of key indicators pertaining to poverty reduction and social equity, ecological preservation, and the implementation of sustainable economic practices. This paper could contribute to an empirically grounded and academically rigorous analysis of the challenges encountered and the accomplishments realized in the domain of sustainable development.